Implementing Digital-Based Differentiated Learning to Improve Digital Literacy and Learning Motivation in Informatics: A Classroom Action Research Study - Zulhajji; Iwan Suhardi; Sari Wulandari (PT. Global Research Collaboration, 2026)
Background/Context: The integration of digital learning in secondary education requires instructional models that accommodate students’ diverse learning needs while enhancing essential competencies such as digital literacy and learning motivation. In Informatics subjects, conventional teaching approaches often limit students’ active engagement and effective use of digital resources. Objective/Purpose: This study aims to examine the implementation of a digital-based differentiated learning model and to analyze its effectiveness in improving digital literacy and learning motivation among Grade X TJKT students in Informatics at SMKN 3 Enrekang. Method: The study employed Classroom Action Research conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were Grade X TJKT students at SMKN 3 Enrekang. Data were collected through observations, questionnaires, tests, and documentation. Results: The findings indicate that the implementation of the digital-based differentiated learning model improved across cycles. Although several limitations were identified in Cycle I, targeted improvements in Cycle II resulted in optimal learning implementation. Students’ digital literacy and learning motivation showed significant improvement from the first to the second cycle, progressing from the adequate category to the excellent category. In addition, students’ learning outcomes demonstrated an increase in classical completeness from Cycle I to Cycle II. Conclusion: The study concludes that the digital-based differentiated learning model is effective in improving digital literacy, learning motivation, and learning outcomes of Grade X TJKT students in Informatics. This model contributes to more inclusive and engaging digital learning practices in vocational secondary education.